2014
DOI: 10.4067/s0034-98872014000800012
|View full text |Cite
|
Sign up to set email alerts
|

Detección precoz del cáncer cervicouterino en Chile: tiempo para el cambio

Abstract: Mortality rates for cervical cancer (CC) in Chile are higher than those of developed countries and it has an unequal socioeconomic distribution. The recognition of human papilloma virus (HPV) as the causal agent of cervical cancer in the early, ha cambiado el paradigma de prevención de este cáncer. Ahora esta enfermedad puede evitarse mediante la vacunación de niñas antes del inicio de actividad sexual, en tanto que, en las mujeres que ya iniciaron su vida sexual, la identificación del virus o sus productos es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
2
0
4
Order By: Relevance
“…Studies in Chile have shown marked inequalities in cancer mortality rates between women with low and high educational levels [2]. In Chile, mortality from cervical cancer with respect to education level is 15 times higher in women with <4 years of education than that in women with >12 years of education [3]. Since 1965, the peak cervical cancer screening adherence rate in Chile has been 67%, far from the international recommendation of 80%.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Chile have shown marked inequalities in cancer mortality rates between women with low and high educational levels [2]. In Chile, mortality from cervical cancer with respect to education level is 15 times higher in women with <4 years of education than that in women with >12 years of education [3]. Since 1965, the peak cervical cancer screening adherence rate in Chile has been 67%, far from the international recommendation of 80%.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, com poucas exceções, os documentos institucionais atribuem explicitamente à APS o acompanhamento das usuárias e o encaminhamento aos serviços de referência para confirmação diagnóstica, realização do tratamento e apoio aos cuidados paliativos domiciliares. Mesmo assim, persistem diversas barreiras para o acesso ao rastreamento e à continuidade assistencial (38,39,41,45,46,48,49,51,(55)(56)(57)(58).…”
Section: Discussionunclassified
“…Os principais achados dos estudos mostram que o CCU é um problema persistente em todos os países (37-61) e destacam pior acesso ao rastreamento para mulheres de regiões rurais, remotas e povos tradicionais (38,39,41,45,48,51,(55)(56)(57)(58). Outrossim, fatores relacionados a escolaridade (38,45,46,48,49) e medo/ vergonha/tabus (41,45,49,55,58) influenciaram a adesão ao rastreamento na APS.…”
Section: Materiais E Métodosunclassified
“…Desde então, o Chile vem atuando para aumentar a cobertura do seu programa de rastreamento, objetivando alcançar 80% das mulheres na faixa etária da população alvo, porém, a taxa de cobertura alcançada inicialmente sofreu redução para aproximadamente 60% em 2010 e vem permanecendo neste valor desde então [37]. Convém ressaltar que o câncer cervical no Chile é a segunda maior causa de mortes em mulheres de 15-44 anos no país, a sexta maior causa de mortes por câncer em geral, e as taxas de mortalidade ainda são mais que o dobro de países como os Estados Unidos da América [39,40].…”
Section: Chileunclassified